2005
DOI: 10.1109/mcse.2005.124
|View full text |Cite
|
Sign up to set email alerts
|

Service-oriented environments for dynamically interacting with mesoscale weather

Abstract: E ach year across the US, mesoscale weather events-flash floods, tornadoes, hail, strong winds, lightning, and localized winter storms-cause hundreds of deaths, routinely disrupt transportation and commerce, and lead to economic losses averaging more than US$13 billion.1 Although mitigating the impacts of such events would yield enormous economic and societal benefits, research leading to that goal is hindered by rigid IT frameworks that can't accommodate the real-time, on-demand, dynamically adaptive needs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 20 publications
(14 reference statements)
0
69
0
Order By: Relevance
“…The limitations of today's static environments were highlighted in §1, and Droegemeier et al (2005) showed real examples in which dynamic adaptation can be of considerable practical benefit. A more complete discussion of dynamic adaptation, including key scientific questions, is presented in §4.…”
Section: Objectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…The limitations of today's static environments were highlighted in §1, and Droegemeier et al (2005) showed real examples in which dynamic adaptation can be of considerable practical benefit. A more complete discussion of dynamic adaptation, including key scientific questions, is presented in §4.…”
Section: Objectivesmentioning
confidence: 99%
“…Because individual services can be concatenated in many different ways (see Droegemeier et al 2005), the LEAD framework provides users with an almost endless set of capabilities ranging from simply accessing the data and perhaps visualizing it to running highly complex and linked data ingest, assimilation and forecast processes in real time, and in a manner that adjusts dynamically to inputs as well as outputs. Further details can be found in Droegemeier et al (2005).…”
Section: The Lead Service-oriented Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these workflow often access shared resources or data and run computations on grid or cloud systems. For example, a weather prediction workflow is triggered by streaming sensor atmospheric data and consists of a number of data-processing steps that use distributed data and resources [8]. This workflow must complete in a timely manner to generate appropriate forecasts and initiate any emergency management measures that might be necessary.…”
Section: Introductionmentioning
confidence: 99%